Ocena jakości życia przed i po protezowaniu narządu słuchu = The impact of hearing aids on the quality of life - Patrycja Witczak; Dominik Olejniczak; Joanna Skonieczna (Kazimierz Wielki University, 2016)
Witczak Patrycja, Olejniczak Dominik, Skonieczna Joanna. Ocena jakości życia przed i po protezowaniu narządu słuchu = The impact of hearing aids on the quality of life. Journal of Education, Health and Sport. 2016;6(9):712-723. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.159211 http://ojs.ukw.edu.pl/index.php/johs/article/view/3895         The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.09.2016. Revised 24.09.2016. Accepted: 24.09.2016.       Ocena jakości życia przed i po protezowaniu narządu słuchu The impact of hearing aids on the quality of life     Patrycja Witczak1, Dominik Olejniczak2, Joanna Skonieczna2     1 Absolwentka kierunku Zdrowie Publiczne Wydział Nauki o Zdrowiu Warszawski Uniwersytet Medyczny   2 Warszawski Uniwersytet Medyczny Zakład Zdrowia Publicznego ul. Banacha 1a, 02-097 Warszawa     Słowa kluczowe: aparaty słuchowe, jakoś życia, niedosłuch Key words: Hearing aids, Quality of life, Hearing impairment     Streszczenie   Wprowadzenie i cel pracy: Problem niedosłuchu dotyczy ok. 12% populacji. Liczba osób dotkniętych wadą słuchu systematycznie wzrasta. Jest to ważny aspekt medyczny i społeczny. U osób u których stwierdzono niedosłuch jedną z metod rehabilitacji narządu słuchu jest użytkowanie aparatu słuchowego. Podstawowym celem protezowania narządu słuchu jest poprawa komunikowania się osoby niedosłyszącej z otoczeniem oraz zwiększenie komfortu jej życia. Głównym celem badania była ocena jakości życia i korzyści z użytkowania aparatów słuchowych u osób po 60 roku życia. Materiał i metoda: Zastosowaną metodą badawczą był sondaż diagnostyczny, techniką ankieta, a narzędziem kwestionariusz standaryzowany oceny jakości życia przed i po protezowaniu narządu słuchu. Grupą badaną jest populacja osób w wieku powyżej 60 lat. Łączna ilość osób przebadanych stanowiła grupę 60 pacjentów z wadami słuchu stosujących aparaty słuchowe. Wyniki: Narażenie środowiska pracy na hałas zadeklarowało blisko 61% badanych. Jedynie 30,5% zna podstawowe uwarunkowania zdrowia mające znaczenie w przypadku niedosłuchu. Około 75% badanych uznało, że aparat słuchowy pomógł im w życiu codziennym przynajmniej w stopniu dobrym. Wnioski: Z uwagi na dużą poprawę jakości życia po protezowaniu narządu słuchu, konieczne jest edukowanie i informowanie pacjentów w zakresie tej metody leczenia i podnoszenia jakości życia, a także szeroko zakrojone działania edukacyjne nakierowane na profilaktykę wad słuchu, skupiające się na minimalizowaniu czynników ryzyka wystąpienia niedosłuchu.     Abstract   Introduction: The problem of hearing impairment relates to approx. 12% of the population. The number of people affected by hearing impairment is steadily increasing. This is an important medical and social aspect. Usage of a hearing aids is one of the methods of rehabilitation people with hearing loss. The primary objective of usage of hearing aids for person with hearing impairment is to improve communication with the environment and increase the comfort of his or her life. The main objective of the study was to assess the quality of life and benefit from the use of hearing aids by people over 60 years old. Material and Methods: Research method - diagnostic survey. The standardized questionnaire assessed quality of life before and after hearing aids usage. Study group was the population of people over the age of 60 years. The total number of people surveyed - 60 patients with hearing problems using hearing aids. Results: Exposure to workplace noise declared nearly 61% of respondents. Only 30.5% of the respondents know the basic determinants of health relevant to the hearing. About 75% of the respondents felt that the hearing aid helped them in their everyday lives at least at good level. Conclusion: Due to the high improvement of quality of life after hearing aids usage, it is necessary to educate and inform patients regarding the treatment and quality of life. We need widespread educational activities aimed at the prevention of hearing defects and focusing on minimizing risk factors for hearing loss.